The effect of physical barriers under a raised house on mosquito entry: an experimental study in rural Gambia - Majo Carrasco-Tenezaca; Musa Jawara; John Bradley; Umberto D’Alessandro; David Jeffries; Jakob B. Knudsen; Steve W. Lindsay (Malaria Journal, 2024)
Abstract Background Anopheles gambiae, the major malaria mosquito in sub-Saharan Africa, feed largely indoors at night. Raising a house off the ground with no barriers underneath reduces mosquito-house entry. This experiment tested whether walling off the space under an elevated hut affects mosquito-hut entry. Methods Four inhabited experimental huts, each of which could be moved up and down, were used in rural Gambia. Nightly collections of mosquitoes were made using light traps and temperature and carbon dioxide levels monitored indoors and outdoors using loggers. Each night, a reference hut was kept at ground level and three huts raised 2 m above the ground; with the space under the hut left open, walled with air-permeable walls or solid walls. Treatments were rotated every four nights using a randomized block design. The experiment was conducted for 32 nights. Primary measurements were mosquito numbers and indoor temperature in each hut. Results A total of 1,259 female Anopheles gambiae sensu lato were collected in the hut at ground level, 655 in the hut with an open ground floor, 981 in the hut with air-permeable walls underneath and 873 in the hut with solid walls underneath. Multivariate analysis, adjusting for confounders, showed that a raised hut open underneath had 53% fewer mosquitoes (95% CI 47–58%), those with air-permeable walls underneath 24% fewer (95% CI 9–36%) and huts with solid walls underneath 31% fewer (95% CI 24–37%) compared with a hut on the ground. Similar results were found for Mansonia spp. and total number of female mosquitoes, but not for Culex mosquitoes where hut entry was unaffected by height or barriers. Indoor temperature and carbon dioxide levels were similar in all huts. Conclusion Raising a house 2 m from the ground reduces the entry of An. gambiae and Mansonia mosquitoes, but not Culex species. The protective effect of height is reduced if the space underneath the hut is walled off.